Plan de mejoramiento del compromiso organizacional para los empleados de la empresa SEGUVID de la ciudad de Ambato. - Aimacaña Mullo, Irma Mélida (2021)
The purpose of this research study was to propose activities for the improvement of organizational commitment for the employees of ‘SEGUVID’ company in the city of Ambato. The problem that was considered to be solved was the lack of commitment in the workers and to look for alternatives to improve through a program of activities in relation to the dimensions of affective, normative and continuity organizational commitment. The methodology was characterized by an exploratory research. The methods used were deductive, inductive. The sample was non-probabilistic because it was a limited group and it was carried out at 30 workers. Among the most outstanding techniques, a questionnaire validated by Meyer and Allen was used and a chi-square was also used to contrast the dependence between organizational commitment and work performance. The results showed that there is a high feeling of emotional attachment in the normative dimension to say that employees feel that they perform their activities out of moral duty. As a proposal, it was designed through Meyer and Allen’s threedimensional model and activities that forge the organizational commitment of workers and improve business productivity. It was concluded that both the hypothesis and the proposed objectives were fulfilled, that is, organizational behavior and organizational performance showed a dependency relationship when contrasted with the chi-square test. The recommendations were aimed to the implementation of the proposal and the motivation for the improvement of efficiency, effectiveness and work environment.